A randomised, controlled trial of once daily and multi-dose daily gentamicin in young Kenyan infants. Issue 7 (21st June 2004) - English, M; Mohammed, S; Ross, A; Ndirangu, S; Kokwaro, G; Shann, F; Marsh, K
Abstract : Aims: To test the suitability of a simple once daily (OD) gentamicin regimen for use in young infants where routine therapeutic drug monitoring is not possible. Methods: In an open, randomised, controlled trial, infants with suspected severe sepsis admitted to a Kenyan, rural district hospital received a novel, OD gentamicin regimen or routine multi-dose (MD) regimens. Results: A total of 297 infants (over 40% ⩽7 days) were randomised per protocol; 292 contributed at least some data for analysis of pharmacological endpoints. One hour after the first dose, 5% (7/136) and 28% (35/123) of infants in OD and MD arms respectively had plasma gentamicin concentrations <4 μg/ml (a surrogate of treatment inadequacy). Geometric mean gentamicin concentrations at this time were 9.0 μg/ml (95% CI 8.3 to 9.9) and 4.7 μg/ml (95% CI 4.2 to 5.3) respectively. By the fourth day, pre-dose concentrations ⩾2 μg/ml (a surrogate of potential treatment toxicity) were found in 6% (5/89) and 24% (21/86) of infants respectively. Mortality was similar in both groups and clinically insignificant, although potential gentamicin induced renal toxicity was observed in <2% infants. Conclusions: A "two, four, six, eight" OD gentamicin regime, appropriate for premature infants and those in the first days and weeks of life, seems a suitable, safe prescribing guide in resource poor settings.